PENGARUH PENGUASAAN BESARAN TERHADAP HASIL BELAJAR FISIKA MATERI HUKUM II NEWTON TENTANG GERAK SISWA KELAS X SMA NEGERI PADANGSIDIMPUAN - Febriani Hastini Nasution (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2022)
The aim of this research was to know whether there was a significant influence between measurement mastery on students achievement in newton’s law II about motion subject at tenth grade students of SMA Negeri 7 Padangsidimpuan. The population of thes research was all the tenth grade students of SMA Negeri 7 Padangsidimpuan which include 6 classes or 100 students. By applying random sampling technique, the writer took the sample 59 students. In collecting the data, the writer used test. Based on the result of this research, measurement mastery had the average 77, it was categorized “good”. While the students achievement in newton law II of motion had the average 72, it was categorized “good”. Based on statistics analysis calcution, it could be gotten that tcount on 9,7, in error level significant 5% confidence level significan 95%, df = N – 2 = 57, it could be gotten that ttable =1,675. It could be seen that ttabel was greater ttable (9,7> 1.675). The alternative hypothesis was accepted. It means that there was a significant influence between measurement mastery on students achievent in Newton law II of motion subject at the tenth grade students of SMA Negeri 7 Padangsidimpuan. The better measurement mastery the better students achievenment in Newtons law II of motion at the tenth grade students of SMA Negeri 7 Padangsidimpuan.